(untitled) (Bangladesh Journal of Agricultural Research, 2008)
Twelve well known mango varieties of Bangladesh (Surjapuri, Ashwina, Kalia, Deori, Fazli, Langra, Lota Bombai, BARI Aam-1, Gopalbhog, Bombai, Khirsapat, and Rani Passand) planted in the research farm of the Horticulture Research Centre of BARI at Joydebpur were evaluated in respect of tree growth, flowering and harvesting time, yield per tree, and quantitative and qualitative characteristics of leaf, inflorescence and fruit. Susceptibility of the varieties to insects and diseases was also observed. Full bloom in all the varieties took place between 26 February to 02 March. Fruits of the varieties were harvested between 24 May and 10 July. The variety Deori was the earliest and Ashwina was the latest in respect of harvesting time. The maximum number of fruits/tree (300) and yield/tree (37.40kg) were produced by Kalia and Ashwina, respectively. The highest fruit weight (315.00g) was obtained from Fazli followed by Ashwina (220.00g), Bombai (207.00g) and Langra (200.00g). The highest percentage of edible portion was recorded in Ashwina (76.00%) followed by Langra (73.00%), Fazli (72.00%, Kalia (71.00%, Bombai (70.50%), Khirsapat (68.50%), Gopalbhog (68.50), and BARI Aam-1 (68.00%). TSS was found to be the highest in Khirsapat (22.00%) whcih was followed by Bombai (19.50%). Langra (18.50%), Gopalbhog and BARI Aam-1 (18.00%). All of the varieties were affected by different insects and diseases in different degrees. In overall performance, the varieties Khirsapat, Gopalbhog, Langra, and BARI Aam-1 were better than the others. Bangladesh J. Agril. Res. 32(4) : 541-552.